Baltic Crusades and Societal Innovation in Medieval Livonia, 1200-1350
1 online resource
Keywords: The Baltic Crusades in the thirteenth century led to the creation of the medieval Livonia. But what happened after the conquest? The contributors to this volume analyse the cultural, societal, economic and technological changes in the Baltic Sea region c. 1200–1350. The chapters focus on innovations and long-term developments which were important in integrating the area into medieval European society more broadly, while also questioning the traditional divide of the Livonian post-crusade society into native victims and foreign victors. The process of multilateral negotiations and adaptions created a synthesis which was not necessarily an outcome of the wars but also a manifestation of universal innovation processes in northern Europe. Contributors are Arvi Haak, Tõnno Jonuks, Kristjan Kaljusaar, Ivar Leimus, Christian Lübke, Madis Maasing, Mihkel Mäesalu, Anti Selart, Vija Stikāne, and Andres Tvauri.